MARINE EXPOSURE TESTS OF COCONUT TIMBER - R. N. Palomar (International Coconut Community Journal, 1987)
Marine exposure tests of sawn coconut lumber were carried out for three years to determine the resistance, of treated coconut timber to marine borers. The test panels measuzing 50 mm x 100 mm x 450 mm, were installed in sea water between October, 1981 and September, 1984. Results showed three promising treatments. These were the vacuum/pressure method using chromated copper arsenate, the modifted double diffusion treatment employing mixture of copper adphate, sodium dichromate and arsenic pentoxide, and the hot and cold bath treatment with coal tar creosote. The specimens treated by these preservative systems showed trace or slight surface infestation while the untreated wood panels indicated from deep and extensive infestation to failure due to attack of marine borers. The perfomance of the treated medium density specimens appeared to be inferior than the hard samples indicating that only the latter materials should be used for marine structures.